2024
DOI: 10.1093/cz/zoae005
|View full text |Cite
|
Sign up to set email alerts
|

Is the speed of adjusting to environmental change condition dependent? An experiment with house mice (Mus musculus)

Karem Lopez-Hervas,
Neelam Porwal,
Mathilde Delacoux
et al.

Abstract: Environmental conditions change constantly either by anthropogenic perturbation or naturally across space and time. Often, a change in behaviour is the first response to changing conditions. Behavioural flexibility can potentially improve an organism’s chances to survive and reproduce. Currently, we lack an understanding on the time-scale such behavioural adjustments need, how they actually affect reproduction and survival and whether behavioural adjustments are sufficient in keeping up with changing condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 59 publications
2
4
2
Order By: Relevance
“…Contrary to previous findings in mice from semi-natural enclosures (Lopez-Hervas et al, 2024;Prabh et al, 2023), we found that cage-housed mice on a high-quality diet covered more distance in the Open Field compared to the standard-quality food group (Figure 1). This result implies that high-quality food promotes an active stress-coping strategy in caged-house mice.…”
Section: Rq1: How Does Behavior Change As a Function Of Food Quality ...contrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to previous findings in mice from semi-natural enclosures (Lopez-Hervas et al, 2024;Prabh et al, 2023), we found that cage-housed mice on a high-quality diet covered more distance in the Open Field compared to the standard-quality food group (Figure 1). This result implies that high-quality food promotes an active stress-coping strategy in caged-house mice.…”
Section: Rq1: How Does Behavior Change As a Function Of Food Quality ...contrasting
confidence: 99%
“…Mice might employ these strategies as an insurance against variation in food quality (Mathot et al, 2012). Mice previously receiving high-quality food have reproductive value to lose and might protect these 'assets' by reducing risky exposure to threats and predators (Clark, 1994;Lopez-Hervas et al, 2024;McElreath et al, 2007;Wolf et al, 2007).…”
Section: A Nutrition-dependent Sensitive Period For Stress-copingmentioning
confidence: 99%
See 3 more Smart Citations